Recent Publications (Quarterly Journal of Economics, 1962)
Journal Article Recent Publications Get access The Quarterly Journal of Economics, Volume 76, Issue 3, August 1962, Pages 508–514, https://doi.org/10.1093/qje/76.3.508 Published: 01 August 1962